PowerPoint-based quizzes in wave motion: Performance and experiences of students - Frank Angelo Abayog Pacala (Intelektual Pustaka Media Utama, 2019)
The effect of PowerPoint Presentation–based (PPPb) quiz to the students’ scores has been rarely studied. It is the intention of this research to understand the effect of PPPb quiz to students score in wave motion and the students’ experiences under such a strategy. This research used a mixed approach: quasi-experimental to learn if scores gain was significant, and thematic analysis was used to know the experiences of the students. The results confirmed that PPPb quiz has indeed increased the scores of the students. Statistical analysis verified that this increase was significant. On the thematic analysis, students manifested comparing oral quiz to PPPb, caught their attention, and vivid communication. Therefore, the effect of PPPb was significant to the students because it positively impacted their scores in wave motion and promoted vivid communication among students.